Marriage forecasting : changing the climate of your relationship one conversation at a time - Muehlhoff, Tim, 1961- (Downers Grove, Ill. : IVP Books, 2010)
Muehlhoff shows how to take an accurate climate reading of a relationship and explains what causes climates of poor communication. With current research on marital communication, listening skills, empathy and conflict resolution, Marriage Forecasting provides practical ways for couples to rebuild a warm relational climate. --from publisher description
What are communication climates? -- Environmental press: why marriage can be a struggle -- Improving your communication climate -- Strengthening trust in your climate -- Talking your way into a supportive climate -- Taking a reading of your marriage -- Calling a truce -- Changing how we view conflict -- Seven principles for making disagreements productive -- The necessity of forgiveness -- Hurricane warnings: when conflict turns to abuse -- Our communication climate with God and why it means everything.
Includes bibliographical references (pages [180]-189) and indexes.
Description based on print version record.
Keywords: Marriage -- Religious aspects -- Christianity; Communication -- Religious aspects -- Christianity; Communication -- Religious aspects -- Christianity; Marriage -- Religious aspects -- Christianity; RELIGION / Christian Life / General; Electronic books